Carbon nanotube filled rubber nanocomposites - K. C, Nimita; Abraham, Jiji; Thomas, Martin George; Vahabi, Henri; Maria, Hanna J.; Thomas, Sabu (Frontiers in Carbon, 2024)
Rubber (elastomer) based polymer nanocomposites have attracted wide range of attention from industries and other fields due to its exceptionally good mechanical, thermal and electrical properties. One of the promising candidates of this category is CNT filled rubber nanocomposites. This review throws light on the historical trajectory of development of CNT filled rubber nanocomposites. Various fabrication methods, detailed explanation of reinforcement mechanism in CNT/ rubber nanocomposites and the relationship between the structure and properties are reviewed. The next part of the review discusses about the morphological and interface characteristics. An attempt to investigate the versatile mechanical, thermal, and electrical properties also included in the review. The final part of the review includes the applications of CNT filled rubber nanocomposites. Major applications in fields like electronics, sustainable biomedical and EMI shielding are discussed in detail. The review also focuses on the key challenges that arises while incorporating CNTs into rubber matrices.